Pelatihan Dan Pendidikan Kesehatan Pada Ibu Post Partum Tentang Pengetahuan Senam Nifas Di Puskesmas Sobel Distrik Teluk Duairi Kabupaten Teluk Wondama - Treasa, Adisty Dwi; Dardi, Satriana; Indriani, Putu Lusita Nati; Sari, Erma Puspita; Buhari, Suharti; Maharani, Dian (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
The postpartum period (Post Partum) is the period that begins after the birth of the placenta and ends when the uterus returns to its normal state before pregnancy, which lasts for 6 weeks or 42 days. The aim of PkM is to provide knowledge and understanding about postpartum exercise, especially to postpartum mothers so they can carry out postpartum exercise. Postpartum exercises are certain body movements carried out by mothers after giving birth until the end of the postpartum period which are aimed at helping to restore the strength of the pelvic floor muscles, tightening the muscles of the abdominal wall and perineum, helping with good body posture and preventing complications. Training methods and health education for post partum mothers regarding knowledge of postpartum exercise at the Sobel Community Health Center, Teluk Duairi District, Teluk Wundama District so that the material presented is easy to understand. The results of community service activities show an increase in knowledge and understanding of the material provided. The material presented can be understood by participants which is felt to be very useful. The postpartum exercise also went well. The conclusion states that the implementation of community service activities with training, health education and postpartum exercise has gone well and smoothly. Postpartum exercise therapy for mothers after giving birth can help the recovery process more quickly.